Análise das alterações hemodinâmicas em ratos geradas pelas peçonhas dos escorpiões centruroides margaritatus, centruroides limpidus e centruroides noxius - Céron, Jessica Dayana Galíndez (2018)
The scorpions from the Centruroides genus present great medical importance due to the high extent of scorpionism and their cardiovascular effects after poisoning. Thus, given the clinical and pharmacological importance of these scorpion venoms, the main objective of this investigation was to determine systemic functional alterations, specifically the cardiovascular ones, for the venoms from Centruroides margaritatus (Cm), Centruroides limpidus (Cl) and Centruroides noxius (Cn) scorpions, using systemic hemodynamic techniques. For this purpose, doses of Cm and Cl at 10, 30, 60, 100 and 300 (μg/kg) and doses of Cn at 1 and 60 (µg/kg) – because of its high toxicity - were administered intravenously (n=6) using Wistar rats as the experimental model (Rattus norvegicus) (310-350 g). We evaluated systolic parameters such as: ejection fraction (EF), stroke work (SW) and maximal slope of the systolic pressure increment (+dP/dt); and diastolic parameters such as dP/dt min and the time constant for isovolumic relaxation (Tau). Additionally, we also evaluated mean arterial pressure (MAP), cardiac output (CO), arterial elastance (AE), central venous pressure (CVP), total peripheral resistance (TPR), left ventricular volume (LVV), heart rate (HR) and electrocardiogram. We evaluated effects of poisoning such as cyanosis, piloerection and fluid secretion, for the three poisons. It was found that Cm venom caused a decrease in the dose of 300 µg/kg of Ea (3,2±0,4) and increased the TC (2666±334) and dp/dt máx (13884±834). The C. limpidus venom caused a decrease in the dose of 100b and 300b µg/kg in parameters like MAP, (79,17±5,48 and 66,80±9,45), HR (229,6±54 and 195,3±35,6) and CO. On the other hand, there was an increase in dP/dt máx, dP/dt min and CVP. For the C. noxius venom evaluation, MAP was decreased in the dose of 10 up to 300 µg/kg, in the same way that TPR. Parameters such as HR decreased in the dose of 100 and 300 µg/kg, as well as CO, EF, dP/dt máx and SW, which was also altered in the dose of 60 µg/kg. The parameter dP/dt min increased from the dose of 60 to 300 µg/kg. Cn venom treated group showed preservation of cardiac architecture regarding heart tissue analysis, although presence of formation of pulmonary edema. The three venoms induced premature ventricular depolarization with all doses evaluated, more often for venoms from Cl and Cn. Therefore, C. margaritatus generate mild cardiotoxicity, unlike C. limpidus which did it moderately and C. noxius was the most toxic with possible left ventricular insufficiency.